Penerapan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Kemampuan Berpikir Analitis Siswa Pada Materi Dinamika Atmosfer Dan Dampaknya Terhadap Kehidupan Kelas X-D Di SMA Negeri 6 Gorontalo Utara - Rahim, Sri Murniyanti; Nurfaika, Nurfaika; Pambudi, Moch. Rio (Universitas Negeri Gorontalo, 2025)
In facing the development of the era in the 21st century, students are required to have special competencies. There are many challenges and problems that must be faced by students in this era. For example, learning materials that are difficult to understand and less in accordance with students' daily lives. The purpose of this study was to determine whether the application of the Problem Based Learning (PBL) Learning Model can improve students' analytical thinking skills in the material of Atmospheric Dynamics and Its Impact on Class X-D Life at SMA Negeri 6 North Gorontalo. The research method uses the type of classroom action research (PTK), this research model follows the Kemmis and McTaggart research model. The results of the study showed that in Cycle 1, the average student score was 73.75, there was an increase in Cycle II with an average of 84.64. This increase was 10.89 points. The percentage increase was 14.76%. The results of this study indicate that the application of PBL is very effective in improving students' analytical thinking skills.